ayee_ciera
  • ayee_ciera
WILL MEDAL AND FAN help pls
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
ayee_ciera
  • ayee_ciera
solve by elimination -2x+2y+3z=0 -2x-y+z=-3 2x+3y+3z=5
anonymous
  • anonymous
Simplifying -2x + 2y + 3z = 0 Solving -2x + 2y + 3z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -2x + 2y + -2y + 3z = 0 + -2y Combine like terms: 2y + -2y = 0 -2x + 0 + 3z = 0 + -2y -2x + 3z = 0 + -2y Remove the zero: -2x + 3z = -2y Add '-3z' to each side of the equation. -2x + 3z + -3z = -2y + -3z Combine like terms: 3z + -3z = 0 -2x + 0 = -2y + -3z -2x = -2y + -3z Divide each side by '-2'. x = y + 1.5z Simplifying x = y + 1.5z
anonymous
  • anonymous
Simplifying -2x + -1y + z = -3 Solving -2x + -1y + z = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. -2x + -1y + y + z = -3 + y Combine like terms: -1y + y = 0 -2x + 0 + z = -3 + y -2x + z = -3 + y Add '-1z' to each side of the equation. -2x + z + -1z = -3 + y + -1z Combine like terms: z + -1z = 0 -2x + 0 = -3 + y + -1z -2x = -3 + y + -1z Divide each side by '-2'. x = 1.5 + -0.5y + 0.5z Simplifying x = 1.5 + -0.5y + 0.5z

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Simplifying 2x + 3y + 3z = 5 Solving 2x + 3y + 3z = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y + 3z = 5 + -3y Combine like terms: 3y + -3y = 0 2x + 0 + 3z = 5 + -3y 2x + 3z = 5 + -3y Add '-3z' to each side of the equation. 2x + 3z + -3z = 5 + -3y + -3z Combine like terms: 3z + -3z = 0 2x + 0 = 5 + -3y + -3z 2x = 5 + -3y + -3z Divide each side by '2'. x = 2.5 + -1.5y + -1.5z Simplifying x = 2.5 + -1.5y + -1.5z
ayee_ciera
  • ayee_ciera
@Peach-es1234 how do i simplify tht??
anonymous
  • anonymous
Each of the responses simplified each of them. -2x+2y+3z=0 -2x-y+z=-3 2x+3y+3z=5

Looking for something else?

Not the answer you are looking for? Search for more explanations.